Mechanical power and mortality: analysis of a prospective cohort of ventilated patients - Pérez Yero, Yudiel; Sosa Remón, Ariel; Auza-Santivañez, Jhossmar Cristians; Cuba Naranjo, Arian Jesús; García Arias, Dasha María; Jeréz Alvarez, Ana Esperanza; Saborit García, Mileydys; Arteaga Iriarte, Osman; Antezana-Muñoz, Jose Bernardo (Multidisciplinar (Montevideo), 2025)
Introduction: Mechanical power establishes the amount of energy per unit time transferred from the ventilator to the respiratory system. Its usefulness as a predictor of death has been demonstrated in COVID-19 or acute respiratory distress syndrome. However, its prognostic value in ventilated patients without these conditions is unknown. Objective: to determine the association of mechanical power with the incidence of mortality in patients with invasive artificial ventilation in the Intensive Care Unit. Methods: a prospective cohort study in 52 patients ventilated invasively in an Intensive Care Unit of a Cuban hospital. The final variable of interest was mortality. Sociodemographic and ventilatory variables were studied. The level of significance was found according to p value ≤ 0.05 through hypothesis testing of differences in means and proportions and the the area under the ROC curve. Results: mortality predominated in female patients, with a mean age of 51.76 ± 21.76 years. The main causes of ventilation were respiratory. High APACHE II score, SOFA and a mean mechanical power value of 14.82 ± 1.67 J/min were associated with mortality. On analysis of the area under the ROC curve, mechanical power yielded adequate discriminative ability for mortality (AROC: 0.993; 95 % CI: 0.979 - 1; p = 0.000). Conclusions: In this series of ventilated patients the mechanical power value proved to be a factor associated with mortality.